2015
DOI: 10.1007/s00371-015-1143-6
|View full text |Cite
|
Sign up to set email alerts
|

Obfuscated volume rendering

Abstract: Analyzing and processing various data types in a privacy-preserving perspective has been researched in many disciplines; however, such an issue draws very limited attention in the research field of scientific visualization. We wondered if it is possible to delegate the rendering of a volume data set to a remote server(s) while still being able to preserve its privacy to certain extent. This paper presents a block-based volume data transformation algorithm that obfuscates a volume data set so as to reduce the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, such information when integrated with openly available attributes, patient identity can be at risk: using small DNA sequences from the Y chromosome, researchers at MIT were able to extract the genealogical information (surname, relatives) and religious background of fifty people from the 1000 Genomes Project [GMG*13]. The same rationale applies to use of shapes in the case of volume rendering [CY16]. In summary, low‐accuracy channels do not guarantee the preservation of privacy and appropriate risks should be assessed in the context of the externally available information about the individuals who are represented.…”
Section: Critical Reflection On the Design Spacementioning
confidence: 99%
“…However, such information when integrated with openly available attributes, patient identity can be at risk: using small DNA sequences from the Y chromosome, researchers at MIT were able to extract the genealogical information (surname, relatives) and religious background of fifty people from the 1000 Genomes Project [GMG*13]. The same rationale applies to use of shapes in the case of volume rendering [CY16]. In summary, low‐accuracy channels do not guarantee the preservation of privacy and appropriate risks should be assessed in the context of the externally available information about the individuals who are represented.…”
Section: Critical Reflection On the Design Spacementioning
confidence: 99%
“…Chou and Yang [3] present a volume rendering approach that attempts to make it difficult for an unintended observer to make sense of the volume dataset that resides on a server. This is done by, on the client's side, subdividing the original data into equally sized blocks.…”
Section: Related Workmentioning
confidence: 99%
“…Since Paillier's cryptosystem does not carry over multiplication of two encrypted values to plaintext, it is classified as a partially homomorphic encryption (PHE) scheme. Paillier can securely encrypt many values (e.g., 512 3 voxels of a volume) from a small number space (e.g., 2 10 possible density values), because it is probabilistic, which means that during the encryption, the obfuscation can map a single plaintext value randomly to a large number of possible encrypted values. This makes a simple "probing" for finding out the number correspondence impossible.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Dasgupta et al [2014] suggested future opportunities and challenges on privacy preserving visualization specifically for the analysis of electronic medical records (EMRs) data. Chou and Yang [2015] and Mohanty et al [2013] enabled the process of volume rendering to be done while keeping the content of the volume dataset to be obscured to unauthorized viewers. In information visualization literature, Dasgupta and Kosara [2011] applied the concepts of kanonymity [Sweeney 2002] and l-diversity [Machanavajjhala et al 2007] and proposed an adaptive visualization technique for privacy preservation in parallel coordinates.…”
Section: Privacy Preserving Data Visualizationmentioning
confidence: 99%